2006
DOI: 10.1017/s0266467406003191
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal shift in the foraging niche of a tropical avian resident: resource competition at work?

Abstract: This study examined the foraging behaviour of a resident bird species, the rufous-capped warbler (RCWA, Basileuterus rufifrons), in a shaded-coffee farm in Chiapas, Mexico. Unlike many resident species that use shaded-coffee agroecosystems seasonally, RCWAs do not move to other habitats when migrants are present. RCWA foraging was compared when migrant birds were present (dry season) and absent (wet season). It was hypothesized that RCWAs would exhibit a seasonal foraging niche shift because of resource compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 38 publications
6
26
0
1
Order By: Relevance
“…Previous observations in shaded coffee farms suggest that arthropod and bird abundances are greater in the canopy rather than the crop layer (Wunderle and Latta 1996, Greenberg et al 1997, Jedlicka et al 2006. We compared bird predation in the canopy and crop layers for three agroforestry studies (Table 1) in Mexico (Philpott et al 2004, Perfecto et al 2007) and in FIG. 1.…”
Section: Bird Effects In the Canopy Vs Understory Layers Of Agroforementioning
confidence: 99%
“…Previous observations in shaded coffee farms suggest that arthropod and bird abundances are greater in the canopy rather than the crop layer (Wunderle and Latta 1996, Greenberg et al 1997, Jedlicka et al 2006. We compared bird predation in the canopy and crop layers for three agroforestry studies (Table 1) in Mexico (Philpott et al 2004, Perfecto et al 2007) and in FIG. 1.…”
Section: Bird Effects In the Canopy Vs Understory Layers Of Agroforementioning
confidence: 99%
“…At one of our study sites, Philpott et al (2004) demonstrated that flying vertebrates depress the abundance of arthropods, including beetles, on branches of Inga shade trees. Jedlicka et al (2006) combined flying vertebrate exclosures in Inga shade trees with a subset of our exclosures in coffee at one of our study sites to show that flying vertebrates significantly depress the abundance of both large (45 mm) and small (o5 mm) arthropods in Inga foliage of the canopy, but not in the coffee foliage of the understory. However, Perfecto et al (2004) demonstrated increased removal rates of lepidopteran larvae, presumably by flying vertebrates, from coffee foliage outside of flying vertebrate exclosures in one of our high-shade sites.…”
Section: Article In Pressmentioning
confidence: 99%
“…Previous studies have suggested that birds and/or bats can significantly depress the abundance of arthropods on the foliage of Inga shade trees in coffee plantations (Philpott et al, 2004), or on the foliage of the coffee bushes, themselves (Greenberg, Bichier, Cruz-Ango´n, MacVean, & Perez et al, 2000;Perfecto et al, 2004). Jedlicka, Greenberg, Perfecto, Philpott, and Dietsch (2006) found that flying vertebrates depressed arthropod abundance in the canopy of Inga shade trees but not in the coffee bushes of the understory. Herein, we add to this emerging picture of top-down effects in coffee agroecosystems by analyzing the effects of flying vertebrate exclusion on the abundance, species richness, and species composition of beetles on coffee foliage.…”
Section: Introductionmentioning
confidence: 96%
“…Resource utilization patterns could also reflect past adaptations to competitive interactions (Connell 1980) or the importance of facilitative interactions (Bertness and Callaway 1994). To date, there have been few empirical tests of the competitive mechanism assumed by niche models (Silvertown 2004), and the few that have been conducted have yielded conflicting results (Hairston 1980a, b;Jedlicka et al 2006;Miller et al 2007;Pacala and Roughgarden 1982;Thomson 2006).…”
Section: Introductionmentioning
confidence: 99%